Sustainability Report, Institutional Ownership, and Foreign Ownership on Financial Performance with Board of Commissioners as Moderating - Laurensia, Laurensia; Lindrawati, Lindrawati; Susanto, Adi (Jurnal Ilmiah Manajemen & Bisnis, 2024)
Company was built with the hope of being able to operate for a long time, so must have good financial performance. In order for financial performance to be improved, company need to issue sustainability reports to provide information to stakeholders, and company also need share ownership by institutional and foreign parties because they are considered capable of influencing the course of company in achieving its goals. However, to achieve these goals company requires strict supervision, which is through board of commissioners. This research aims to analyze the effect of sustainability reports, institutional ownership, and foreign ownership on financial performance with board of commissioners as moderating. Research design used is quantitative research. Research object are manufacturing companies listed on Indonesia Stock Exchange with 214 observations. Data analysis technique used is multiple linear regression analysis and moderation. Research results showed that sustainability report and foreign ownership have no effect on financial performance both ROA and ROE, and institutional ownership have a positive effect on financial performance both ROA and ROE with t are 2.892 and 1.983. Board of commissioners was unable to moderate the effect of foreign ownership on financial performance both ROA and ROE. Board of commissioners was able to moderate the effect of sustainability report on financial performance in ROA but weaken with t is negative 2.534, and was unable to moderate the effect on sustainability report to financial performance in ROE. Board of commissioners was able to moderate the effect of institutional ownership on financial performance in ROA with t is positive 2.128, but was unable to moderate on financial performance in ROE.